Nano-silica modified polyethylene oxide electrolyte diaphragm based on bacterial silk cellulose matrix, preparation method and battery thereof
By generating nanosilicon dioxide in situ in the solution of bacterial hypha cellulose and polyethylene oxide, the problems of poor mechanical properties of electrolyte separators and nanoparticle agglomeration are solved, the cycle life and conductivity of lithium-ion batteries are improved, and super-enabled Preparation of thin electrolyte separators is suitable for high-performance development and commercialization of batteries.
Patent Information
- Application Number
- CN202411387136.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the mechanical properties of the polyethylene oxide electrolyte membrane are poor, resulting in insufficient cycle stability of lithium symmetric batteries, and nanoparticles are prone to agglomeration in aqueous solutions, affecting conductivity and crystallinity.
Nanosilicon dioxide is generated in situ in an alkaline mixed solution of hypha cellulose and polyethylene oxide. By hydrolyzing silicic acid, uniformly distributed nanoparticles are formed, the mechanical strength and conductivity of the electrolyte membrane are improved, and the aggregation of nanoparticles is reduced. .
It significantly improves the cycle life and conductivity of lithium-ion batteries, enhances the mechanical and interface performance of lithium-symmetric batteries, and realizes the preparation of ultra-thin electrolyte separators, which are suitable for large-scale production.
Smart Images

Figure CN119253049A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of electrochemical energy storage polymer solid electrolyte membranes, and in particular to a nano-silicon dioxide-modified polyethylene oxide electrolyte diaphragm based on a bacterial silk cellulose matrix, a preparation method and a battery thereof. Background Art
[0002] In order to improve the mechanical properties of polyethylene oxide (PEO), it is usually necessary to add a matrix material during the preparation of PEO electrolyte membranes. Bacterial cellulose (BC) is a matrix material with many excellent properties. It has good miscibility with PEO, is easy to process, has strong mechanical properties and excellent stability. Therefore, it plays an important role in improving the mechanical properties of electrolytes as a matrix material.
[0003] During the preparation of the electrolyte membrane, the electrolyte membrane produced when the BC content is high has strong mechanical strength, and an ultra-thin electrolyte membrane can be prepared to achieve a long cycle life.
[0004] Tan, X et al. prepared a composite polymer electrolyte membrane by synthesizing SiO2 through an in-situ non-hydrolytic sol-gel reaction (Tan, X. et al. Preparation of Nanocomposite Polymer Electrolyte via In Situ Synthesis of SiO2 Nanoparticles in PEO. Nanomaterials 10, doi: 10.3390 / nano10010157 (2020)), and the conductivity is two orders of magnitude higher than that of the pre-synthesized composite polymer electrolyte. However, due to the poor mechanical properties of the solid electrolyte membrane and the contact problem of the interface impedance, the lithium symmetric battery can only cycle for 700 hours, and the cycle stability needs to be further improved. In addition, the method of synthesizing SiO2 through an in-situ non-hydrolytic sol-gel reaction is complicated to operate and is not conducive to large-scale production.
[0005] The mechanical properties of the electrolyte can be improved by adding BC, and ultra-thin electrolyte membranes can be prepared by tape casting. However, the addition of BC will increase the crystallinity of PEO, causing the conductivity to decrease and the battery to not cycle properly. Therefore, nanoparticles are generally added for modification. Conventional nanoparticles have a small molecular diameter and a large surface energy, making them easy to agglomerate and unable to reduce the crystallinity of PEO. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a polyethylene oxide electrolyte membrane modified with nano-silica based on a bacterial silk cellulose matrix, a preparation method and a battery thereof, wherein silicic acid is added to an alkaline mixed solution of bacterial silk cellulose and polyethylene oxide, and the silicic acid undergoes a hydrolysis reaction in the mixed solution to generate nano-silica, and lithium salt is added after the hydrolysis and mixing are complete to prepare a solid electrolyte membrane; the present invention fully utilizes the excellent dispersibility of in-situ generated nanoparticles in aqueous solutions, and the advantage of bacterial silk cellulose having strong mechanical strength and being able to prepare ultra-thin electrolyte membranes, reduces the agglomeration of nanoparticles, achieves uniform distribution of nanoparticles in aqueous solutions, and improves the surface conductivity of the electrolyte membrane; the present invention also provides a battery prepared using the solid electrolyte membrane.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on a bacterial silk cellulose matrix, wherein the raw materials include bacterial silk cellulose, polyethylene oxide, a solvent, an alkaline substance, a silicate substance and a lithium salt; in terms of mass ratio, the bacterial silk cellulose: polyethylene oxide: solvent: silicate substance: lithium salt = (1-3): 20: (60-100): (4-8): (6-16), and the amount of the alkaline substance added is determined according to the pH value of the solution after addition being 11.
[0009] The solvent is a mixture of one or more of deionized water, ethanol, ethylene glycol, N-methylpyrrolidone, and N,N-dimethylformamide in any ratio.
[0010] The alkaline substance is a mixture of one or more of ammonia water, sodium carbonate and sodium bicarbonate in any ratio.
[0011] The silicic acid material is a mixture of one or more of silicic acid and tetraethyl orthosilicate in any ratio.
[0012] The lithium salt is a mixture of one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium perchlorate (LiClO4), and lithium bisfluorosulfonyl imide (LiFSI) in any ratio.
[0013] A method for preparing a polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on the bacterial silk cellulose matrix comprises the following steps:
[0014] Step 1, taking bacterial silk cellulose: polyethylene oxide: solvent: silicate substance: lithium salt in a mass ratio of (1-3): 20: (60-100): (4-8): (6-16);
[0015] Wherein, bacterial silk cellulose: polyethylene oxide: solvent = (1-3): 20: (60-100), bacterial silk cellulose and polyethylene oxide are dispersed in the solvent to obtain a mixed solution A;
[0016] Step 2, adding alkaline substances to the mixed solution A prepared in step 1 until the solution pH value reaches 11 and silicate substances with a mass ratio of (4-8), mixing them evenly, to obtain a mixed solution B;
[0017] Step 3, placing the mixed solution B obtained in step 2 at 60-80° C. for hydrolysis reaction, so that the silicic acid substance in the mixed solution B is hydrolyzed into silicon dioxide, to obtain a mixed solution C;
[0018] Step 4, adding a lithium salt having a mass ratio of (6-16) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0019] Step 5, using the electrolyte precursor solution obtained in step 4 to prepare an electrolyte separator by scraping;
[0020] Step 6, preliminarily drying the electrolyte membrane obtained in step 5;
[0021] Step 7, peel off the electrolyte membrane obtained in step 6 and dry it again.
[0022] The solvent in step 1 is a mixture of one or more of deionized water, ethanol, ethylene glycol, N-methylpyrrolidone, and N,N-dimethylformamide in any ratio;
[0023] The alkaline substance in step 2 is a mixture of one or more of ammonia water, sodium carbonate and sodium bicarbonate in any ratio;
[0024] The silicic acid substance in step 2 is a mixture of one or more of silicic acid and tetraethyl orthosilicate in any ratio;
[0025] The lithium salt in step 4 is a mixture of one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), and lithium bis(fluorosulfonyl)imide (LiFSI) in any ratio.
[0026] The dispersion method in step 1 uses one of magnetic stirring, mechanical stirring, ultrasonic dispersion, and heating.
[0027] In step 5, the scraping is uniform and the thickness does not exceed 20um;
[0028] In step 6, the initial drying temperature is set to 60-80°C, and the initial drying time is 10-20 minutes;
[0029] In step 7, the re-drying temperature is set at 80-100° C., and the re-drying time is 24 h to 48 h.
[0030] A solid-state lithium-ion battery comprises the above-mentioned nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on bacterial silk cellulose matrix.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] 1. The present invention discloses a method for preparing a polyethylene oxide electrolyte membrane modified with nano-silica based on a bacterial silk cellulose matrix, which uses a method for in-situ generation of nano-silica in a mixed solution of bacterial silk cellulose BC and polyethylene oxide PEO, thereby avoiding the problem of agglomeration of nanoparticles directly added in an aqueous solution and improving the dispersibility of the nanoparticles.
[0033] 2. The addition of bacterial silk cellulose BC in the present invention greatly improves the mechanical strength of the PEO electrolyte membrane, increases the crystallinity of the electrolyte, and thus reduces the conductivity of the electrolyte. At the same time, when the BC content is 20%, the lithium symmetric battery at this time cannot perform normal lithium metal deposition and stripping at 60°C. At the same time, thanks to the improvement of mechanical properties, the cycle life of the lithium metal symmetric battery can reach 1330h. It makes it possible to prepare ultra-thin solid electrolytes.
[0034] 3. The present invention adopts a method of in-situ generation of nano-silicon dioxide to solve the problem of easy aggregation of nano-silicon dioxide in bacterial silk cellulose BC PEO aqueous solution, and greatly improves the conductivity of the electrolyte.
[0035] 4. The present invention adds silicate to a mixed solution of bacterial silk cellulose and an alkaline substance of polyethylene oxide, and hydrolyzes silica in the mixed solution to generate nano-silicon dioxide, which can significantly reduce the crystallinity of PEO electrolyte, enhance the lithium ion transmission capacity, and improve the conductivity, thereby improving the interface performance as a whole.
[0036] In summary, the present invention utilizes bacterial silk cellulose BC as a matrix material and generates nano-silicon dioxide through in-situ silicic acid hydrolysis to prepare a PEO-based electrolyte. Not only can an electrolyte membrane with excellent mechanical properties and cycle performance be obtained, but the process is also simple and rapid. It is an effective and economical method for preparing a solid electrolyte membrane. This invention has a promoting and guiding role in the development and commercialization of high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the appearance of the prepared BC PEO nano-silica lithium salt electrolyte membrane.
[0038] Figure 2is the thickness of the prepared BC PEO nano-silica lithium salt electrolyte membrane.
[0039] Figure 3 SEM surface and silicon element distribution of the prepared BC PEO nano-silica lithium salt electrolyte membrane.
[0040] Figure 4 The lithium symmetric cycling voltage curves at 60°C of the electrolyte membranes prepared under different conditions. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0042] Example 1
[0043] A nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on a bacterial silk cellulose matrix, wherein the raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, a solvent (deionized water), an alkaline substance (ammonia water), a silicate substance (tetraethyl orthosilicate) and a lithium salt (LiTFSI); by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (deionized water): silicate substance (tetraethyl orthosilicate): lithium salt (LiTFSI) = 1:20:60:4:6; the alkaline substance (ammonia water) is added until the pH of the solution is 11.
[0044] A method for preparing a polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on a bacterial silk cellulose matrix comprises the following steps:
[0045] Step 1, taking bacterial silk cellulose: polyethylene oxide: solvent (deionized water): silicate (tetraethyl orthosilicate): lithium salt (LiTFSI) = 1:20:60:4:6 by mass ratio;
[0046] Dispersing bacterial silk cellulose and polyethylene oxide in a solvent to obtain a mixed solution A; in terms of mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (deionized water) = 1:20:60;
[0047] Step 2, adding alkaline substance (ammonia water) to the mixed solution A prepared in step 1 until the pH value is 11 and silicate substance (tetraethyl orthosilicate) with a mass ratio of 4 in sequence, mixing evenly, to obtain a mixed solution B;
[0048] Step 3, placing the mixed solution B obtained in step 2 at 60° C. for hydrolysis reaction, so that the silicic acid substance (tetraethyl orthosilicate) in the mixed solution B is hydrolyzed into silicon dioxide, thereby obtaining a mixed solution C;
[0049] Step 4, adding 6% by weight of lithium salt to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0050] Step 5, using the electrolyte precursor solution obtained in step 4, using a scraper coating method, scraping it evenly with a thickness not exceeding 20 μm to prepare an electrolyte separator;
[0051] Step 6, placing the electrolyte membrane obtained in step 5 in a forced air oven for preliminary drying, with the oven temperature set at 60° C. and the drying time set at 10 min;
[0052] Step 7, peel off the electrolyte membrane obtained in step 6, put it into a vacuum oven for drying again, and set the drying temperature to 80°C and the drying time to 24h.
[0053] Example 2
[0054] A nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on a bacterial silk cellulose matrix, wherein the raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, a solvent (ethylene glycol), an alkaline substance (ammonia water), a silicic acid substance (tetraethyl orthosilicate) and a lithium salt (LiTFSI); by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (ethylene glycol): silicic acid substance (tetraethyl orthosilicate): lithium salt (LiTFSI) = 2:20:70:5:8; the amount of alkaline substance (ammonia water) added is determined according to the pH value of the solution after addition being 11.
[0055] A method for preparing a polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on a bacterial silk cellulose matrix comprises the following steps:
[0056] Step 1, taking bacterial silk cellulose: polyethylene oxide: solvent (ethylene glycol): silicate (tetraethyl orthosilicate): lithium salt (LiTFSI) = 2:20:70:5:8 by mass ratio;
[0057] Dispersing bacterial silk cellulose and polyethylene oxide in a solvent to obtain a mixed solution A; in terms of mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (ethylene glycol) = 2:20:70;
[0058] Step 2, adding alkaline substance (ammonia water) to the mixed solution A prepared in step 1 until the solution pH value is 11 and silicate substance (tetraethyl orthosilicate) with a mass ratio of 5, and mixing well to obtain a mixed solution B;
[0059] Step 3, placing the mixed solution B obtained in step 2 at 65° C. for hydrolysis reaction, so that the silicic acid substance (tetraethyl orthosilicate) in the mixed solution B is hydrolyzed into silicon dioxide, to obtain a mixed solution C;
[0060] Step 4, adding 8% by weight of lithium salt (LiTFSI) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0061] Step 5, using the electrolyte precursor solution obtained in step 4, using a scraper coating method, scraping it evenly with a thickness not exceeding 20 μm to prepare an electrolyte separator;
[0062] Step 6, placing the electrolyte membrane obtained in step 5 in a forced air oven for preliminary drying, with the oven temperature set at 65° C. and the drying time set at 12 min;
[0063] Step 7, peel off the electrolyte membrane obtained in step 6, put it into a vacuum oven for drying again, and set the drying temperature to 85°C and the drying time to 28h.
[0064] Example 3
[0065] A nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on a bacterial silk cellulose matrix, wherein the raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, solvent (deionized water), alkaline substance (ammonia water), silicate substance (tetraethyl orthosilicate) and lithium salt (LiClO4); by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (deionized water): silicate substance (tetraethyl orthosilicate): lithium salt (LiClO4) = 2:20:80:6:10, and the amount of alkaline substance (ammonia water) added is determined according to the pH value of the solution after addition being 11.
[0066] A method for preparing a polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on a bacterial silk cellulose matrix comprises the following steps:
[0067] Step 1, taking bacterial silk cellulose: polyethylene oxide: solvent (deionized water): silicate (tetraethyl orthosilicate): lithium salt (LiClO4) = 2:20:80:6:10 by mass ratio;
[0068] Dispersing bacterial silk cellulose and polyethylene oxide in a solvent to obtain a mixed solution A; in terms of mass ratio, bacterial silk cellulose: polyethylene oxide: solvent = 2:20:80;
[0069] Step 2, adding alkaline substance (ammonia water) to the mixed solution A prepared in step 1 until the solution pH value is 11 and silicate substance (tetraethyl orthosilicate) with a mass ratio of 6, and mixing them evenly to obtain a mixed solution B;
[0070] Step 3, placing the mixed solution B obtained in step 2 at 70° C. for hydrolysis reaction, so that the silicic acid substance (tetraethyl orthosilicate) in the mixed solution B is hydrolyzed into silicon dioxide, thereby obtaining a mixed solution C;
[0071] Step 4, adding 10% by weight of lithium salt (LiClO4) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0072] Step 5, using the electrolyte precursor solution obtained in step 4, using a scraper coating method, scraping it evenly with a thickness not exceeding 20 μm to prepare an electrolyte separator;
[0073] Step 6, placing the electrolyte membrane obtained in step 5 in a forced air oven for preliminary drying, with the oven temperature set at 70° C. and the drying time set at 15 min;
[0074] Step 7, peel off the electrolyte membrane obtained in step 6, put it into a vacuum oven for drying again, and set the drying temperature to 90°C and the drying time to 32h.
[0075] Example 4
[0076] A nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on a bacterial silk cellulose matrix, wherein the raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, a solvent (N,N-dimethylformamide), an alkaline substance (ammonia water), a silicic acid substance (tetraethyl orthosilicate) and a lithium salt (LiTFSI); by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (N,N-dimethylformamide): silicic acid substance (tetraethyl orthosilicate): lithium salt (LiTFSI) = 3:20:90:7:13; the amount of alkaline substance (ammonia water) added is determined according to the pH value of the solution after addition being 11.
[0077] A method for preparing a polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on a bacterial silk cellulose matrix comprises the following steps:
[0078] Step 1, taking bacterial silk cellulose, polyethylene oxide, solvent (N,N-dimethylformamide), silicic acid substance (tetraethyl orthosilicate) and lithium salt (LiTFSI) in a mass ratio of 3:20:90:7:13;
[0079] The bacterial silk cellulose and polyethylene oxide are dispersed in a solvent (N,N-dimethylformamide) to obtain a mixed solution A; in terms of mass ratio, the bacterial silk cellulose: polyethylene oxide: solvent = 3:20:90;
[0080] Step 2, adding alkaline substance (ammonia water) to the mixed solution A prepared in step 1 until the solution pH value is 11 and silicate substance (tetraethyl orthosilicate) with a mass ratio of 7, and mixing well to obtain a mixed solution B;
[0081] Step 3, placing the mixed solution B obtained in step 2 at 75° C. for hydrolysis reaction, so that the silicic acid substance (tetraethyl orthosilicate) in the mixed solution B is hydrolyzed into silicon dioxide, thereby obtaining a mixed solution C;
[0082] Step 4, adding 13% by weight of lithium salt (LiTFSI) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0083] Step 5, using the electrolyte precursor solution obtained in step 4, using a scraper coating method, scraping it evenly with a thickness not exceeding 20 μm to prepare an electrolyte separator;
[0084] Step 6, placing the electrolyte membrane obtained in step 5 in a forced air oven for preliminary drying, with the oven temperature set at 75° C. and the drying time set at 17 min;
[0085] Step 7, peel off the electrolyte membrane obtained in step 6, put it into a vacuum oven for drying again, and set the drying temperature to 95°C and the drying time to 38 hours.
[0086] Example 5
[0087] A nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on a bacterial silk cellulose matrix, wherein the raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, a solvent (N,N-dimethylformamide), an alkaline substance (ammonia water), a silicic acid substance (tetraethyl orthosilicate) and a lithium salt (LiFSI); by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (N,N-dimethylformamide): silicic acid substance (tetraethyl orthosilicate): lithium salt (LiFSI) = 3:20:100:8:16, and the amount of alkaline substance (ammonia water) added is determined according to the pH value of the solution after addition being 11.
[0088] A method for preparing a polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on a bacterial silk cellulose matrix comprises the following steps:
[0089] Step 1, taking bacterial silk cellulose, polyethylene oxide, solvent (N,N-dimethylformamide), alkaline substance (ammonia water) and silicate substance (tetraethyl orthosilicate): lithium salt (LiFSI) = 3:20:100:8:16 according to the mass ratio;
[0090] Dispersing bacterial silk cellulose and polyethylene oxide in a solvent to obtain a mixed solution A; in terms of mass ratio, bacterial silk cellulose: polyethylene oxide: solvent (N,N-dimethylformamide) = 3:20:100;
[0091] Step 2, adding alkaline substance (ammonia water) to the mixed solution A prepared in step 1 until the solution pH value is 11 and silicate substance with a mass ratio of 8, and mixing them evenly to obtain a mixed solution B;
[0092] Step 3, placing the mixed solution B obtained in step 2 at 80° C. for hydrolysis reaction, so that the silicic acid substance (tetraethyl orthosilicate) in the mixed solution B is hydrolyzed into silicon dioxide, thereby obtaining a mixed solution C;
[0093] Step 4, adding 16% by weight of lithium salt (LiFSI) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution;
[0094] Step 5, using the electrolyte precursor solution obtained in step 4, using a scraper coating method, scraping it evenly with a thickness not exceeding 20 μm to prepare an electrolyte separator;
[0095] Step 6, placing the electrolyte membrane obtained in step 5 in a forced air oven for preliminary drying, with the oven temperature set at 80° C. and the drying time set at 20 min;
[0096] Step 7, peel off the electrolyte membrane obtained in step 6, put it into a vacuum oven for drying again, and set the drying temperature to 100° C. and the drying time to 42 hours.
[0097] Principle of the invention:
[0098] When the concentration of bacterial cellulose is 10%, compared with the unmodified electrolyte membrane, the cycle life is only about 450 hours. However, the lithium symmetric battery assembled with 10% in-situ generated nano-silica electrolyte film has a cycle life of nearly 700 hours. At the same time, the voltage during lithium metal deposition is only 16mV, indicating that at this time, due to the effect of nano-silica, the interface performance is improved, and the cycle performance of the lithium symmetric battery is also improved.
[0099] The addition of BC will increase the crystallinity of the electrolyte, thereby reducing the conductivity of the electrolyte. At the same time, when the BC content is 20%, the lithium symmetric battery cannot perform normal lithium metal deposition and stripping at 60°C. At the same time, thanks to the improvement of mechanical properties, the cycle life of the lithium metal symmetric battery can reach 1330h.
[0100] The present invention adds silicate to a mixed solution of bacterial silk cellulose and polyethylene oxide alkaline substances, and the silicate is hydrolyzed in the mixed solution to generate nano-silicon dioxide. The method can significantly reduce the crystallinity of polyethylene oxide electrolyte, enhance the lithium ion transmission capacity, and improve the conductivity, thereby improving the interface performance as a whole. The test results of the prepared lithium symmetrical battery at 60°C are as follows: Figure 4 As shown in the figure, compared with the unmodified electrolyte membrane, the cycle life of the in-situ generated nano-silicon dioxide is nearly 1330h, and the voltage during lithium metal deposition is only 16mV, indicating that the interface performance is improved due to the effect of nano-silicon dioxide, and the cycle performance of the lithium symmetric battery is also improved. Figure 2 As shown, the thickness of the electrolyte membrane measured by a thickness gauge is only 11 μm.
[0101] Figure 1The ultra-thin polyethylene oxide electrolyte film with added nano-silicon dioxide prepared in Example 1 of the present invention has excellent mechanical strength and is very suitable for battery assembly and even large-scale production applications.
[0102] Figure 3 To use a desktop scanning electron microscope Figure 1 The morphological analysis of the ultra-thin polyethylene oxide electrolyte film with added nano-silicon dioxide revealed that the electrolyte surface was very uniform and smooth, and energy spectrum scanning revealed that the silicon element was very evenly distributed inside the electrolyte.
Claims
1. A polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on bacterial silk cellulose matrix, characterized in that: The raw materials of the electrolyte membrane include bacterial silk cellulose, polyethylene oxide, solvent, alkaline substance, silicate substance and lithium salt; calculated by mass ratio, bacterial silk cellulose: polyethylene oxide: solvent: silicate substance: lithium salt = (1-3): 20: (60-100): (4-8): (6-16), and the amount of alkaline substance added is determined according to the pH value of the solution after addition being 11.
2. The polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on bacterial silk cellulose matrix according to claim 1, characterized in that: The solvent is a mixture of one or more of deionized water, ethanol, ethylene glycol, N-methylpyrrolidone, and N,N-dimethylformamide in any ratio.
3. The polyethylene oxide electrolyte membrane modified by nano-silicon dioxide based on bacterial silk cellulose matrix according to claim 1, characterized in that: The alkaline substance is a mixture of one or more of ammonia water, sodium carbonate and sodium bicarbonate in any ratio.
4. The nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on bacterial silk cellulose matrix according to claim 1, characterized in that: The silicic acid material is a mixture of one or more of silicic acid and tetraethyl orthosilicate in any ratio.
5. The nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on bacterial silk cellulose matrix according to claim 1, characterized in that: The lithium salt is a mixture of one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium perchlorate (LiClO4), and lithium bisfluorosulfonyl imide (LiFSI) in any ratio.
6. A method for preparing a polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on a bacterial silk cellulose matrix according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, taking bacterial silk cellulose: polyethylene oxide: solvent: silicate substance: lithium salt in a mass ratio of (1-3): 20: (60-100): (4-8): (6-16); Wherein, bacterial silk cellulose: polyethylene oxide: solvent = (1-3): 20: (60-100), bacterial silk cellulose and polyethylene oxide are dispersed in the solvent to obtain a mixed solution A; Step 2, adding alkaline substances to the mixed solution A prepared in step 1 until the solution pH value reaches 11 and silicate substances with a mass ratio of (4-8), mixing them evenly, to obtain a mixed solution B; Step 3, placing the mixed solution B obtained in step 2 at 60-80° C. for hydrolysis reaction, so that the silicic acid substance in the mixed solution B is hydrolyzed into silicon dioxide, to obtain a mixed solution C; Step 4, adding a lithium salt having a mass ratio of (6-16) to the mixed solution C prepared in step 3 to obtain an electrolyte precursor solution; Step 5, using the electrolyte precursor solution obtained in step 4 to prepare an electrolyte separator by scraping; Step 6, preliminarily drying the electrolyte membrane obtained in step 5; Step 7, peel off the electrolyte membrane obtained in step 6 and dry it again.
7. The method for preparing a nano-silicon dioxide-modified polyethylene oxide electrolyte membrane based on bacterial silk cellulose matrix according to claim 6, characterized in that: The solvent in step 1 is a mixture of one or more of deionized water, ethanol, ethylene glycol, N-methylpyrrolidone, and N,N-dimethylformamide in any ratio; The alkaline substance in step 2 is a mixture of one or more of ammonia water, sodium carbonate and sodium bicarbonate in any ratio; The silicic acid substance in step 2 is a mixture of one or more of silicic acid and tetraethyl orthosilicate in any ratio; The lithium salt in step 4 is a mixture of one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), and lithium bis(fluorosulfonyl)imide (LiFSI) in any ratio.
8. The method for preparing a polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on a bacterial silk cellulose matrix according to claim 6, characterized in that: The dispersion method in step 1 uses one of magnetic stirring, mechanical stirring, ultrasonic dispersion, and heating.
9. The method for preparing a polyethylene oxide electrolyte membrane modified with nano-silicon dioxide based on a bacterial silk cellulose matrix according to claim 6, characterized in that: In step 5, the coating is uniform and the thickness does not exceed 20 μm; In step 6, the initial drying temperature is set to 60-80°C, and the initial drying time is 10-20 minutes; In step 7, the re-drying temperature is set at 80-100° C., and the re-drying time is 24 h to 48 h.
10. A solid-state lithium-ion battery, characterized in that: It comprises the polyethylene oxide electrolyte membrane modified with nano-silica based on a bacterial silk cellulose matrix as described in any one of claims 1 to 5 or the polyethylene oxide electrolyte membrane modified with nano-silica based on a bacterial silk cellulose matrix prepared by any one of claims 6 to 9.
Citation Information
Patent Citations
Preparation method and application of nano bacterial cellulose / polyoxyethylene composite solid electrolyte
CN111969246A
In-situ generated silicon dioxide composite solid polymer electrolyte and application thereof in lithium battery
CN114335695A
